Shariah Governance in Islamic Banking: A Study on the Challenges and Best Practices in Indonesia - Sothy, Chak; Dara, Ravi; Alves, Livia (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Shariah governance is a cornerstone of Islamic banking, ensuring compliance with Islamic principles and maintaining stakeholder trust. Indonesia, as a leading player in the global Islamic finance industry, faces unique challenges in implementing effective Shariah governance frameworks. This study examines the challenges and best practices in Shariah governance within Indonesia’s Islamic banking sector. The research aims to identify the key challenges in Shariah governance, analyze best practices, and provide recommendations for enhancing the effectiveness of Shariah governance frameworks in Indonesia’s Islamic banking sector. A mixed-methods approach is employed, combining document analysis of regulatory frameworks, case studies of leading Islamic banks, and in-depth interviews with Shariah scholars, regulators, and banking professionals. Data were analyzed using thematic analysis for qualitative insights and comparative analysis for quantitative data. The findings reveal that Indonesia’s Islamic banking sector faces challenges such as regulatory inconsistencies, limited expertise in Shariah governance, and weak enforcement mechanisms. However, best practices such as centralized Shariah boards, transparent reporting, and stakeholder engagement have been identified as effective strategies for enhancing Shariah governance. This study highlights the importance of addressing regulatory gaps, building capacity in Shariah governance, and adopting best practices to strengthen Indonesia’s Islamic banking sector. By improving